INVESTIGATING THE CONTRAST OF SURFACE MARKING ON DIFFERENT COLOR CONNECTORS FOR TELECOMMUNICATIONS NEEDS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The development of marking technologies for telecommunications connectors requires increasingly detailed information about their applications. One solution is to use QR codes that contain sufficient information about the connectors' applications. Accurate marking of connectors requires a precise marking system, such as a laser marking system. In this study, a Rofin PowerLine F20 Varia fiber laser was used to mark four different types of ABS plastic connectors in various colors. To achieve optimal marking for all four colors, three experiments were conducted to achieve contrasting marking and high roughness. Easy QR code reading was achieved with an average marking power of 3 W to 4.2 W, a laser marking speed of 300 mm/s to 500 mm/s, and a scanning frequency of 50 kHz to 70 kHz at a constant pulse duration of 8 ns and raster spacing of 50 µm. The microstructural changes and change in roughness were determined using a laser scanning microscope (Olympus OLS5000), which revealed structural changes on the surface and an increase in relative roughness from 39% to 76%. This experiment shows that different parameters of the laser marking mode are required for each color.